Molecular dynamics study of palladium clusters: size dependent analysis of structural stabilities and energetics of Pdn (n ≤ 40) via a Lennard-Jones type potential - Boyukata, Mustafa (Array, 2008)
Summary: Possible stable structures and energetics of palladium clusters, Pdn (n = 2–40), have been investigated by performing molecular-dynamics simulations based on a Lennard-Jones type pairpotential. To determine a preferable growth mechanism, the growing pattern of Pdn clusters was analyzed via rearrangement collisions and the simple quenching technique. Main observed results are that palladium clusters prefer three-dimensional structures and spherical clusters of medium size appear to have five-fold symmetry. The results are compared with those from previous theoretical studies